Servius Tullius peut-il être identifié à Mastarna ? - Łoś, Andrzej (Polskie Towarzystwo Filologiczne, 2023)
Servius Tullius is a most fascinating figure from early Roman history. Much controversy and debate has revolved around almost every aspect of his life, particularly his ancestry, ethnicity and his path to power. There are conflicting narratives even within the annalistic tradition. It should, however, be emphasised that there is a wholly different account, deriving from Etruscan sources, of who Servius Tullius was and how he came to power. Many modern scholars prefer the Etruscan version of the career of Servius Tullius to his rise to power in the Roman state. Others think that the complete rejection of Roman tradition is too radical a step. The question I try to answer in this paper is whether it is possible to reconcile the two traditions. The key to my argument is the interpretation of the paintings from the tomb François at Vulci, and in particular the scene of the fight between Marce Camitlnas and Cneve Tarchunies. Cneve Tarchunies would be brother or cousin of Tarquin the Elder, who, on the latter’s dea h, attempted to seize power at the head of his own personal army composed of young Etruscan aristocrats. Servius Tullius and his Etruscan allies, including the brothers Vibenna, would have succeeded in bringing about his defeat and death. But this reconstruction of Servius Tullius’ path to power is also only a hypothesis. Thus, the career of the penultimate Roman king remains a mystery.